Financial conflicts of interest and reporting bias regarding the association between sugar-sweetened beverages and weight gain: a systematic review of systematic reviews. - Maira Bes-Rastrollo (Public Library of Science (PLoS), 2013)
Background Industry sponsors' financial interests might bias the conclusions of scientific research. We examined whether financial industry funding or the disclosure of potential conflicts of interest influenced the results of published systematic reviews (SRs) conducted in the field of sugar-sweetened beverages (SSBs) and weight gain or obesity. Methods and findings We conducted a search of the PubMed, Cochrane Library, and Scopus databases to identify published SRs from the inception of the databases to August 31, 2013, on the association between SSB consumption and weight gain or obesity. SR conclusions were independently classified by two researchers into two groups: those that found a positive association and those that did not. These two reviewers were blinded with respect to the stated source of funding and the disclosure of conflicts of interest. We identified 17 SRs (with 18 conclusions). In six of the SRs a financial conflict of interest with some food industry was disclosed. Among those reviews without any reported conflict of interest, 83.3% of the conclusions (10/12) were that SSB consumption could be a potential risk factor for weight gain. In contrast, the same percentage of conclusions, 83.3% (5/6), of those SRs disclosing some financial conflict of interest with the food industry were that the scientific evidence was insufficient to support a positive association between SSB consumption and weight gain or obesity. Those reviews with conflicts of interest were five times more likely to present a conclusion of no positive association than those without them (relative risk: 5.0, 95% CI: 1.3-19.3). An important limitation of this study is the impossibility of ruling out the existence of publication bias among those studies not declaring any conflict of interest. However, the best large randomized trials also support a direct association between SSB consumption and weight gain or obesity. Conclusions Financial conflicts of interest may bias conclusions from SRs on SSB consumption and weight gain or obesity.